A Review Study of Cold Spray Coating Process - Singh, Harvinder; Singh, Rajdeep (Asian Review of Mechanical Engineering, 2019)
Cold Spray coatings is a material deposition technique from the broad family of thermal spray coatings with the difference of depositing spray particles at the temperature below melting point as it is a solid state process. The spray particles are impinged on the substrate with supersonic velocities. This paper imparts some light on application of this emerging technique with pros and cons. As this technique come up from last 20 years yet practical area is limited and confined to some research only. As this is a quite beneficial technique and help require from public/private sector to commercialize this technique and hope in coming years it comes up with a good growth in this area.